Impacts of COVID-19 on food systems and poverty in Nigeria - Andam, Kwaw S.; Edeh, Hyacinth O.; Oboh, Victor; Pauw, Karl; Thurlow, James (Academic Press, 2020)
Most countries exempted agri-food systems from “lockdown” policies introduced in early 2020 to curb the COVID-19 outbreak. Yet these policies had economywide implications, implying that even exempted sectors were indirectly affected by disruptions to supply chains and falling consumer demand. After its first confirmed case, Nigeria's federal and state governments implemented lockdowns across most cities and states. This included closing all borders and many non-essential businesses. Nigeria also faced declining remittances and export demand caused by the global recission. We estimate the economywide impacts of these lockdown policies and global shocks using a multiplier model of Nigeria calibrated to a 2018 social accounting matrix. We simulate Nigeria's 8-week lockdown (March–June), as well as “recovery” scenarios until the end of 2020. Simulations draw on information from official data, policy announcements, and interviews with government agencies and private sector and industry groups. Findings indicate that total GDP fell 23% during the lockdown. Agri-food system GDP fell 11%, primarily due to restrictions on food services. Household incomes also fell by a quarter, leading a 9% points increase in the national poverty rate. Given the scale of these economic losses, our recovery scenarios indicate that, even with a rapid easing of restrictions and global recovery, Nigeria is unlikely to escape a deep economic recession. We conclude that, while food systems were exempt, they were not immune to the effects of COVID-19. Protecting food supplies should be a priority alongside government efforts to address the health consequences of the pandemic.